Child sexual abuse in religious institutions: A comparative study based on sentences in Spain - Tamarit, Josep M. (European journal of criminology, 2023)
Child sexual abuse is a global problem that has several physical and psychological health implications for the victims. This study aimed to analyse the way criminal courts respond to allegations of child sexual abuse in religious institutions in Spain compared with cases of abuse committed in other institutional contexts. The sample is composed of 97 abusers from three institutional settings (religious institutions, educational centres, sports centres), responsible for a total of 335 child sexual abuse victims. Some of the results are similar to those found in other countries regarding the sex and age of the victims. There is a predominance of abuse involving bodily contact but without penetration, the abusers? profiles are diverse, high exposure to minors was paramount as a risk factor, and there is a higher prevalence of diocesan priest abusers compared with members of religious orders. Significant differences were found between the three institutional groups (that is, religious, educational, and sports) in terms of penalties and civil compensation orders imposed on the abusers. The criminal courts consider sexual abuse committed by religious leaders to be a more severe form of the crime compared with abuse committed in other environments. Our study also revealed that several factors substantially influence the criminal courts? response (for example, proven psychological harm, continuing crime, and the act of penetration), resulting in longer prison sentences and higher civil compensation. The practical implications of these findings are discussed.